2019
DOI: 10.1111/jdi.13011
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection, eradication and diabetes mellitus

Abstract: Aims/Introduction It is suspected that Helicobacter pylori is associated with extradigestive diseases including diabetes. So far, a number of studies have examined the association between H. pylori and diabetes, and the results were conflicting. The aim of the present study was to examine the association between H. pylori infection, eradication and diabetes. Materials and Methods The present cross‐sectional study was carried out using data from annual health checkups carried out at the Toranomon Hospital Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
1
22
0
2
Order By: Relevance
“…Multivariate regression analysis confirmed that H pylori infection was related to DM (OR, 1.25; 95% CI, 1.15-1.35), especially in participants aged ≥ 44 years. 12 Interestingly, in Japan, the risk of DM decreased from 1.36 (95% CI, 1.10-1.67) to 0.92 (95% CI, 0.79-1.07) after H pylori eradication, 13 concordant with the findings that H pylori eradication decreased HbA1c levels in diabetic patients. 14…”
Section: Diabetessupporting
confidence: 72%
“…Multivariate regression analysis confirmed that H pylori infection was related to DM (OR, 1.25; 95% CI, 1.15-1.35), especially in participants aged ≥ 44 years. 12 Interestingly, in Japan, the risk of DM decreased from 1.36 (95% CI, 1.10-1.67) to 0.92 (95% CI, 0.79-1.07) after H pylori eradication, 13 concordant with the findings that H pylori eradication decreased HbA1c levels in diabetic patients. 14…”
Section: Diabetessupporting
confidence: 72%
“…It is estimated that about 4.4 billion people worldwide were infected with H. pylori in 2015 [42], and it is estimated that diabetes will reach 552 million by 2020 [43]. Kato et al have shown that H. pylori infection is associated with an increased risk of diabetes mellitus [44]. Refaeli et al showed that the prevalence of metabolic syndrome in H. pylori-infected patients was higher than that in uninfected patients [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested an association between H pylori , a common infection throughout the world, and glycemic control, insulin resistance, and T2D 17‐20 . On the other hand, some studies concluded that there was no such relationship 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Another significant limitation of the study was that the H pylori infection was determined only with stool antigen test (without using UBT or histopathological tests) were also among the limitations of the study. This test has been reported to have false‐negative results when the antigens in stool are diluted, which might have influenced the results as they were not confirmed with another method of detection 18 …”
Section: Discussionmentioning
confidence: 99%